2019
DOI: 10.3390/rs11242954
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Satellite Based Inland Water Algal Bloom Alerting System Using Analysis Ready Data

Abstract: Water managers need tools to assist in the management of ever increasing algal bloom problems over wide spatial areas to complement sparse and declining in situ monitoring networks. Optical methods employing satellite data offer rapid and widespread coverage for early detection of bloom events. The advent of the Analysis Ready Data (ARD) and Open Data Cube concepts offer the means to lower the technical challenges confronting managers, allowing them to adopt satellite tools. Exploiting Landsat ARD integrated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…While research efforts are still ongoing to face the challenges typical of EO of inland waters, such as global chlorophyll-a concentration mapping or corrections for adjacency effects [26][27][28][29][30], it is also true that depending on an optical sensor's specifications, the EO-derived products vary from turbidity, transparency, and concentrations of chlorophyll, suspended particulate matter and colored dissolved organic matter, floating materials and, in the case of shallow waters, bottom depth and type. In the literature of the past and recent years, numerous articles and reviews [31] and reference therein addressed the optical water quality parameters that can be retrieved by remote sensing techniques (i.e., suspended sediments (turbidity), chlorophyll and other secondary pigments, color dissolved organic matter (CDOM), water clarity and temperature) (e.g., [13,32,33]), the different properties of sensors and platforms and their environmental applications (e.g., [34][35][36]) and the algorithms developed and implemented to retrieve water quality products (e.g., [37][38][39]). For the ecological analysis and correct management of lake ecosystems, it is of great importance to also have information on the benthic component of coastal areas and the presence of aquatic macrophytes.…”
Section: Introductionmentioning
confidence: 99%
“…While research efforts are still ongoing to face the challenges typical of EO of inland waters, such as global chlorophyll-a concentration mapping or corrections for adjacency effects [26][27][28][29][30], it is also true that depending on an optical sensor's specifications, the EO-derived products vary from turbidity, transparency, and concentrations of chlorophyll, suspended particulate matter and colored dissolved organic matter, floating materials and, in the case of shallow waters, bottom depth and type. In the literature of the past and recent years, numerous articles and reviews [31] and reference therein addressed the optical water quality parameters that can be retrieved by remote sensing techniques (i.e., suspended sediments (turbidity), chlorophyll and other secondary pigments, color dissolved organic matter (CDOM), water clarity and temperature) (e.g., [13,32,33]), the different properties of sensors and platforms and their environmental applications (e.g., [34][35][36]) and the algorithms developed and implemented to retrieve water quality products (e.g., [37][38][39]). For the ecological analysis and correct management of lake ecosystems, it is of great importance to also have information on the benthic component of coastal areas and the presence of aquatic macrophytes.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, multiple studies have shown that coupling of in situ spectral measurements to satellite data leads to an inland water monitoring system with high potential [16][17][18][19][20][21][22]. In Australia, the first steps towards such a system have been taken [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the resolution of these products is insufficient for small urban waterbodies. Recently, satellite products with higher resolution, such as Landsat and Sentinel, are increasingly being used to identify harmful algal blooms (Clark et al., 2017; Malthus et al., 2019; Toming et al., 2016). Algorithms have been developed for both coastal and inland freshwaters (Ho et al., 2017).…”
Section: Discussionmentioning
confidence: 99%